2004
DOI: 10.5713/ajas.2004.1219
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of 10 Indigenous Pig Breeds in China by Using Microsatellite Markers

Abstract: The genetic diversities of 10 Chinese pig populations were analyzed by using microsatellite DNA polymorphisms. The results showed that the mean heterozygosities of the 10 populations were between 0.4561 and 0.6446, the mean polymorphism information contents were 0.4241-0.6184 and the mean effective number of alleles were 2.4295-3.7573. These indicated that the genetic diversity of local Chinese pigs was high. The clustering of the 10 populations was nearly inaccordance with their geographical distributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 9 publications
5
14
0
Order By: Relevance
“…Parameters of genetic diversity among European breeds were within previously reported ranges (Table 1) [21][22][23], although among Chinese breeds, the H O value of Meishan pigs was lower than that shown in previous studies [23,24]. N A and N E values in Jinhua pigs were lower than in previous studies [25,26], whereas the corresponding H O value was higher. Agu pigs had lower N E than European breeds and Ryukyu wild boar.…”
Section: Genetic Diversity Within Agu Pigssupporting
confidence: 72%
“…Parameters of genetic diversity among European breeds were within previously reported ranges (Table 1) [21][22][23], although among Chinese breeds, the H O value of Meishan pigs was lower than that shown in previous studies [23,24]. N A and N E values in Jinhua pigs were lower than in previous studies [25,26], whereas the corresponding H O value was higher. Agu pigs had lower N E than European breeds and Ryukyu wild boar.…”
Section: Genetic Diversity Within Agu Pigssupporting
confidence: 72%
“…The PIC value can range from 0 to 1, however, range of PIC estimates in this study were ranging from 0.41(Sw2008) to 0.86 (S0218) for Niang Megha whereas from 0.45 (S0026) to 0.88 (S0005) in Tenyi Vo with mean of 0.65 ±0.03 and 0.68± 0.0.03, respectively. Similar results were also reported in other pigs (Laval et al, 2000;Martinez et al, 2000;Behl et al, 2002;Li et al, 2010;Wang et al, 2004). Most of the markers had PIC values higher than 0.5, which is a useful indicator of genetic variability and forms the basis for developing breeding or genetic improvement strategy for a population.…”
Section: Polymorphic Information Content (Pic)supporting
confidence: 83%
“…Similar values were also reported by other studies. (Li et al, 2010;Li et al, 2015;Wang et al, 2004 andWang et al, 2011) Genetic bottleneck analysis: In a recently bottlenecked population, the observed gene diversity is higher than the expected equilibrium gene diversity because the allele numbers is reduced faster than the gene diversity which can be computed from the Na, under the assumption of a constant-size (equilibrium) population (Luikart et al, 1998a). In a population at mutation-drift equilibrium, there is approximately an equal probability that a locus shows gene diversity excess or a gene diversity deficit.…”
Section: F Estimatesmentioning
confidence: 99%
“…Wang et al (0.6446), but Diannan small-ear pigs are higher than their reported (0.5950)[25].Interpopulation genetic diversityGenetic diversity across breedsExcept for Mingguang small-ear pigs, the rest of the breeds in this study are clearly classified have a clear classification in "Animal Genetics Resources in China Pigs" [26]. The Mingguang small-ear pigs are mainly bred in Mingguang towns and other areas in Tengchong County, Yunnan province.…”
mentioning
confidence: 74%